IMPLEMENTATION OF NIK TO NPWP MATCHING AS AN ADMINISTRATIVE REFORM EFFORT IN TAXATION - Reigiana, Vinka; Riyanto, Slamet; Edrisy, Ibrahim Fikma (Fakultas Hukum Universitas Swadaya Gunung Jati, 2025)
This research aims to analyze the implementation of matching the Population Identification Number (NIK) to the Taxpayer Identification Number (NPWP) as an effort to reform tax administration in Indonesia. The method used is normative research, namely by analyzing legal documents such as related laws and regulations. The discussion includes the implementation of matching NIK and NPWP in increasing the accuracy of tax data, the challenges faced in the implementation process, as well as solutions that can be applied to overcome these problems. The research results show that matching NIK to NPWP can increase efficiency and transparency in tax administration, even though there are challenges such as building and maintaining public trust, as well as a lack of public understanding, and technical problems in the integration system. Therefore, intensive outreach and strengthening of information technology infrastructure is needed to ensure successful implementation. The conclusion of this research confirms that matching NIK to NPWP is a strategic step in creating a better, transparent and accountable tax system, and can minimize the potential for tax leakage in Indonesia.